User Preferences in a Carrageenan-Based Vaginal Drug Delivery System - Li, Bangde (Public Library of Science, 2013)
Topical microbicides are a promising solution to address the global threat of HIV and other sexually transmitted infections. To be successful, a microbicide not only needs to be biologically functional but also highly acceptable to users. User acceptability of microbicides can be incorporated early in the product formulation and design process. Previous qualitative research revealed women had strong preferences regarding product shape, while preferences related to size and firmness were less clear. Here, we explored the effect of size and firmness on the acceptability of semisolid ovoid microbicide prototypes intended for vaginal use. Sexually active women (n = 74) were randomized to one of two conditions: with and without applicator. Nine different prototypes were evaluated; they were formulated to low, medium and high firmness using mixtures of kappa and iota carrageenan and potassium chloride. Three sizes were produced at each firmness level. Women manipulated all nine prototypes, rating them for perceived effectiveness, imagined ease-of-insertion and willingness-to-try on visual analog scales. The influence of size and firmness on these three outcome measures were assessed using ANOVA and response surface models. Results indicated size and firmness both influenced the outcome measures, but firmess was more influential than size. Also, the specific effects of size and firmness depended strongly on presence or absence of an applicator. Generally, women in the without applicator condition wanted a larger, firmer product. Collectively, these data suggest efforts to rationally design of microbicides for enhanced user acceptability must consider factors like size and firmness. Also, the decision to include or forego an applicator should be addressed early in the design process, as it strongly influences other design decisions.